Precise preparation method of small part

By using a pressure chamber with low thermal conductivity, alloy powder and ultrasonic action in the preparation of small parts, a mixed melt above the liquid phase line and performing low-speed and high-speed injection, the problems of air rolling, oxidation and precrystallization in the preparation of small parts are solved, and high-strength and precision preparation effects are achieved.

CN119525468AActive Publication Date: 2025-02-28GUANGZHOU ZHONGSHAN FASTENER CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411792148.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing semi-solid forming technology is difficult to be suitable for the preparation of small-volume semi-solid slurries, which is prone to winding, oxidation and precrystallization, resulting in large differences between batches of small parts and affecting their application.

Method used

A pressure chamber with an inner surface thermal conductivity of <5W/m·K was used to add liquid alloy and alloy powder to the pressure chamber, and ultrasonic action was applied to form a mixed melt above the liquid phase line. Small parts with high strength were prepared by low-speed and high-speed pressure injection and pressure-keeping cooling.

Benefits of technology

It effectively prevents local supercooling and precrystallization, forms a uniform substance and temperature field, inhibits the roseification and dendrosis of the primary phase, and obtains a semi-solid slurry with high fluidity and high strength, ensuring the precision preparation of small parts and the stability between batches.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119525468A_ABST
    Figure CN119525468A_ABST
Patent Text Reader

Abstract

The invention relates to a precise preparation method of a small part, which comprises the following steps: preheating a pressure chamber to 300-400 DEG C, adding a liquid alloy which is 20-40 DEG C higher than a liquidus into the pressure chamber, adding alloy powder with the average particle size of 5-20 microns, and applying ultrasonic action to the liquid alloy to form a mixed melt which is 5-10 DEG C higher than the liquidus, and carrying out low-speed injection on the mixed melt within 5S, then carrying out high-speed injection on the mixed melt, and carrying out pressure maintaining and cooling to obtain the small part. Wherein the mass of the alloy powder is 2-10% of the mass of the liquid alloy, the rate of the low-speed injection is 0.05-0.1 m / s, the rate of the high-speed injection is 2-10 m / s, the time of the low-speed injection is 4-8 S, and the heat conductivity coefficient of the inner surface of the pressure chamber is smaller than 5 W / m.K.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semi-solid alloy materials, in particular to a precision preparation method for small parts. Background Art

[0002] At present, semi-solid forming technology is mainly used for medium and large volume castings. This is because the common semi-solid slurry making methods, such as mechanical stirring method, double helix stirring method, cooling chute method, electromagnetic stirring method, etc., are not suitable for the preparation of small volume semi-solid slurry. The preparation process of small volume semi-solid slurry is prone to air entrainment, oxidation and pre-crystallization. In addition, during the transfer of the slurry, local overcooling is prone to occur when the slurry contacts the wall of the transfer container, resulting in the formation of coarse crystals.

[0003] During the semi-solid casting process of small parts such as mobile phone frames, mid-plates and tablet frames, the solid phase fraction and crystal structure of large volume slurry are prone to change during the long pouring process, resulting in large differences between batches, affecting the application of semi-solid technology on small parts.

[0004] Therefore, it is necessary to provide a method for the precise preparation of small parts. Summary of the invention

[0005] In order to prepare small parts with high strength, it is necessary to provide a precise preparation method for small parts.

[0006] A precision preparation method for small parts, characterized in that it includes the following steps: preheating a pressure chamber to 0-10°C above the liquidus of a liquid alloy, adding a liquid alloy 20-40°C above the liquidus into the pressure chamber, adding an alloy powder with an average particle size of 5-20 μm into the pressure chamber and applying ultrasound to the liquid alloy to form a mixed melt 5-10°C above the liquidus, performing low-speed injection on the mixed melt within 5S, and then performing high-speed injection on the mixed melt, and obtaining the small parts after pressure-maintaining cooling; wherein the mass of the alloy powder is 2-10% of the mass of the liquid alloy, the rate of the low-speed injection is 0.05-0.1m / s, the rate of the high-speed injection is 2-10m / s, the time of the low-speed injection is 4-8S, and the thermal conductivity of the inner surface of the pressure chamber is <5W / m·K.

[0007] This scheme uses a pressure chamber with an inner surface thermal conductivity of less than 5W / m·K to prevent the liquid alloy from being locally supercooled and forming pre-crystallization after contacting the inner wall of the pressure chamber. In the process of adding liquid alloy to the pressure chamber, alloy powder is added and ultrasonic action is applied to make the alloy powder evenly distributed in the liquid alloy to form a mixed melt 5-10°C above the liquidus line. At this time, the alloy powder and the liquid alloy have not yet fully exchanged heat. First, low-speed injection is used to avoid air entrainment of the mixed melt with a low solid phase fraction. During low-speed injection, under the shear force provided by the injection and the local supercooling provided by the alloy powder, The liquid phase components in the mixed melt form new crystal nuclei, and the evenly distributed alloy powder provides a uniform temperature field for the mixed melt. The liquid phase components nucleate around the alloy powder, so the mixed melt as a whole has a relatively uniform material field. The uniform temperature field and material field as well as the heterogeneous nucleation effect provided by the alloy powder form a refined primary phase and inhibit the rosetting and dendrite formation of the primary phase to form equiaxed crystals, thereby obtaining a semi-solid slurry with high fluidity. During high-speed injection, the semi-solid slurry with high fluidity can fully fill the interior of the mold, and ultimately obtain high-strength precision small parts.

[0008] Furthermore, the average particle size of the alloy powder is 5-10 μm. Alloy powders with an average particle size that is too large have a small specific surface area, poor heat exchange efficiency, and are difficult to obtain a large degree of supercooling to promote the formation of crystal nuclei. In addition, crystal nuclei are easily attached to the alloy powder, further affecting the heat exchange efficiency. Alloy powders with an average particle size that is too small are difficult to disperse evenly, resulting in uneven distribution of the alloy powder, thereby affecting the generation of crystal nuclei.

[0009] Furthermore, the mass of the alloy powder is 5%-10% of the mass of the liquid alloy. If the mass of the alloy powder is too low, it is difficult to obtain a large degree of supercooling, and it is even impossible to reduce the temperature of the mixed melt to the semi-solid range; if the mass of the alloy powder is too high, the mixed melt may be cooled to the semi-solid range during the mixing process, and coarsened grains are easily generated under the weak shear force provided by the mixing.

[0010] Furthermore, the temperature of the alloy powder is 20-100° C. If the temperature of the alloy powder is too high, it is difficult to provide a faster heat exchange effect and form a larger supercooling degree; if the temperature of the alloy powder is too low, additional costs will be required.

[0011] Furthermore, the high-speed injection rate is 5-8 m / s. The above injection rate can better fill the mold.

[0012] Furthermore, the inner surface of the pressure chamber is coated with a heat-insulating ceramic material. Heat-insulating ceramic materials, such as TBCs, ZrO2-based ceramic materials, etc., have a thermal conductivity lower than 10W / m·K, or even lower than 1W / m·K, and can withstand high temperature and high pressure.

[0013] Furthermore, the frequency of the ultrasound is 15-35kHz, and the power of the ultrasound is 1000-2000W.

[0014] Furthermore, the holding pressure is 150-200 MPa, and the holding time is 10-20 seconds. The above holding parameters can allow the mixed melt to fully fill the mold.

[0015] Furthermore, the composition of the liquid alloy includes: 6.5-7.5% silicon, 0.3-0.45% magnesium, 0-0.12% iron, 0-0.05% manganese, 0-0.1% copper, 0-0.05% zinc, 0-0.2% titanium and the balance aluminum. The above materials have good fluidity at semi-solid temperature and can fully fill the mold.

[0016] Furthermore, the alloy powder contains 1-3% by mass of a refiner. The alloy powder containing the refiner can not only play a heterogeneous nucleation role, but also partially dissolve the refiner in the mixed melt to inhibit the growth of grains. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram of the metallographic structure of the casting prepared in Example 1.

[0018] Figure 2 This is a schematic diagram of the metallographic structure of the casting prepared in Comparative Example 1. DETAILED DESCRIPTION

[0019] For ease of understanding of the application, the application will be described more fully below. The application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.

[0020] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0022] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0023] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0024] The percentage contents involved in this application, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.

[0025] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.

[0026] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.

[0027] The "particles" mentioned in this application, or materials with a defined particle size distribution, are not necessarily spherical in shape, but may be irregular, primary particles or secondary particles. The particle size of irregular particles is the average of their maximum diameter and minimum diameter.

[0028] Example 1: The composition of the liquid alloy (the percentages of the components involved in the examples and comparative examples are all weight fractions) is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, strontium: 0.0001%, and the rest is aluminum. According to the composition of the liquid alloy, various metals are weighed and mixed, heated to 650°C, and slag and degassing are performed to form a liquid alloy, which is then cooled to 40°C above the liquidus and kept warm.

[0029] The composition of the alloy powder is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, calcium: 1%, and the rest is aluminum. According to the composition of the alloy powder, various metals are weighed and mixed, heated to 650°C, and deslag and degas to form a liquid, and then formed into powder by spraying, and sieved to obtain an alloy powder with an average particle size of 5μm.

[0030] The press chamber was preheated to 400°C (the interior of the press chamber was coated with a TBCs coating (yttria-stabilized zirconia YSZ coating) with a thermal conductivity of 0.93 W / m·K), 2 kg of liquid alloy and 0.1 kg of alloy powder were poured into the press chamber, and ultrasonic action was applied to the liquid alloy to form a mixed melt, wherein the frequency of the ultrasonic action was 35 kHz and the power was 1000 W, and the mixed melt was quickly (within 5 s, wherein the conditions of the embodiment and the comparative example were the same) subjected to low-speed injection (at this time, the temperature of the mixed melt was 5°C above the liquidus line), and the mixed melt was subjected to low-speed injection. The rapid injection rate is 0.05m / s, the low-speed injection time is 8s, the high-speed injection rate is 10m / s, and the high-speed injection is performed until the mixed slurry fully fills the mold, and then the pressure is maintained. The holding pressure is 200MPa and the holding time is 10S to obtain small parts (the small parts in this embodiment and other embodiments and comparative examples are all mobile phone frames. Those skilled in the art can understand that this scheme can be applied to semi-solid casting of other small parts, such as mobile phone mid-plates, tablet computer frames, small medical devices and other small parts).

[0031] Example 2: The composition of the liquid alloy is: silicon: 6.5%, nickel: 0.02%, magnesium: 0.45%, copper: 0.01%, iron: 0.12%, zinc: 0.05%, titanium: 0.20%, manganese: 0.005%, strontium: 0.0001%, and the rest is aluminum. According to the composition of the liquid alloy, various metals are weighed and mixed, heated to 650°C, and slag and gas are removed to form a liquid alloy, which is then cooled to 40°C above the liquidus and kept warm.

[0032] The composition of the alloy powder is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, calcium: 1%, and the rest is aluminum. According to the composition of the alloy powder, various metals are weighed and mixed, heated to 650°C, and deslag and degas to form a liquid, and then formed into powder by spraying, and sieved to obtain an alloy powder with an average particle size of 5μm.

[0033] The press chamber is preheated to 400°C (the interior of the press chamber is coated with TBCs coating (yttria-stabilized zirconia YSZ coating), with a thermal conductivity of 0.93W / m·K), 2kg of liquid alloy and 0.1kg of alloy powder are poured into the press chamber, and ultrasonic action is applied to the liquid alloy to form a mixed melt, wherein the frequency of the ultrasonic action is 15kHz, and the power is 2000W. The mixed melt is quickly subjected to low-speed injection (at this time, the temperature of the mixed melt is 5°C above the liquidus line), the low-speed injection rate is 0.1m / s, the low-speed injection time is 5s, the high-speed injection rate is 2m / s, and the high-speed injection is performed until the mixed slurry fully fills the mold, and then the pressure is maintained, the holding pressure is 200MPa, and the holding time is 10S, so as to obtain small parts.

[0034] Example 3: The composition of the liquid alloy is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, strontium: 0.0001%, and the rest is aluminum. According to the composition of the liquid alloy, various metals are weighed and mixed, heated to 650°C, and slag and degassing are performed to form a liquid alloy, which is then cooled to 40°C above the liquidus and kept warm.

[0035] The composition of the alloy powder is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, calcium: 3%, and the rest is aluminum. According to the composition of the alloy powder, various metals are weighed and mixed, heated to 650°C, and deslag and degas to form a liquid, and then formed into powder by spraying, and sieved to obtain an alloy powder with an average particle size of 5μm.

[0036] The press chamber is preheated to 300°C (the interior of the press chamber is coated with TBCs coating (yttria-stabilized zirconia YSZ coating), with a thermal conductivity of 0.93W / m·K), 2kg of liquid alloy and 0.1kg of alloy powder are poured into the press chamber, and ultrasonic action is applied to the liquid alloy to form a mixed melt, wherein the frequency of the ultrasonic action is 35kHz, and the power is 1000W. The mixed melt is quickly subjected to low-speed injection (at this time, the temperature of the mixed melt is 5°C above the liquidus line), the low-speed injection rate is 0.05m / s, the low-speed injection time is 8s, the high-speed injection rate is 10m / s, and the high-speed injection is performed until the mixed slurry fully fills the mold, and then the pressure is maintained, the holding pressure is 150MPa, and the holding time is 20S, so as to obtain small parts.

[0037] Example 4: The composition of the liquid alloy is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, strontium: 0.0001%, and the rest is aluminum. According to the composition of the liquid alloy, various metals are weighed and mixed, heated to 650°C, and slag and degassing are performed to form a liquid alloy, which is then cooled to 40°C above the liquidus and kept warm.

[0038] The composition of the alloy powder is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, calcium: 1%, and the rest is aluminum. According to the composition of the alloy powder, various metals are weighed and mixed, heated to 650°C, and deslag and degas to form a liquid, and then formed into powder by spraying, and sieved to obtain an alloy powder with an average particle size of 20μm.

[0039] The press chamber is preheated to 400°C (the interior of the press chamber is coated with TBCs coating (yttria-stabilized zirconia YSZ coating), with a thermal conductivity of 0.93W / m·K), 2kg of liquid alloy and 0.1kg of alloy powder are poured into the press chamber, and ultrasonic action is applied to the liquid alloy to form a mixed melt, wherein the frequency of the ultrasonic action is 35kHz, and the power is 1000W. The mixed melt is quickly subjected to low-speed injection (at this time, the temperature of the mixed melt is 5°C above the liquidus line), the low-speed injection rate is 0.05m / s, the low-speed injection time is 8s, the high-speed injection rate is 10m / s, and the high-speed injection is performed until the mixed slurry fully fills the mold, and then the pressure is maintained, the holding pressure is 200MPa, and the holding time is 10S, so as to obtain small parts.

[0040] Example 5: The composition of the liquid alloy is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, strontium: 0.0001%, and the rest is aluminum. According to the composition of the liquid alloy, various metals are weighed and mixed, heated to 650°C, and slag and gas are removed to form a liquid alloy, and then cooled to 20°C above the liquidus and kept warm.

[0041] The composition of the alloy powder is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, calcium: 1%, and the rest is aluminum. According to the composition of the alloy powder, various metals are weighed and mixed, heated to 650°C, and deslag and degas to form a liquid, and then formed into powder by spraying, and sieved to obtain an alloy powder with an average particle size of 5μm.

[0042] The press chamber is preheated to 400°C (the interior of the press chamber is coated with TBCs coating (yttria-stabilized zirconia YSZ coating), with a thermal conductivity of 0.93W / m·K), 2kg of liquid alloy and 0.2kg of alloy powder are poured into the press chamber, and ultrasonic action is applied to the liquid alloy to form a mixed melt, wherein the frequency of the ultrasonic action is 35kHz, and the power is 1000W. The mixed melt is quickly subjected to low-speed injection (at this time, the temperature of the mixed melt is 5°C above the liquidus line), the low-speed injection rate is 0.05m / s, the low-speed injection time is 8s, the high-speed injection rate is 10m / s, and the high-speed injection is performed until the mixed slurry fully fills the mold, and then the pressure is maintained, the holding pressure is 200MPa, and the holding time is 10S, so as to obtain small parts.

[0043] Example 6: The composition of the liquid alloy is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, strontium: 0.0001%, and the rest is aluminum. According to the composition of the liquid alloy, various metals are weighed and mixed, heated to 650°C, and slag and gas are removed to form a liquid alloy, which is then cooled to 40°C above the liquidus and kept warm.

[0044] The composition of the alloy powder is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, calcium: 1%, and the rest is aluminum. According to the composition of the alloy powder, various metals are weighed and mixed, heated to 650°C, and deslag and degas to form a liquid, and then formed into powder by spraying, and sieved to obtain an alloy powder with an average particle size of 5μm.

[0045] The press chamber is preheated to 400°C (the interior of the press chamber is coated with TBCs coating (yttria-stabilized zirconia YSZ coating), with a thermal conductivity of 0.93W / m·K), 2kg of liquid alloy and 0.04kg of alloy powder are poured into the press chamber, and ultrasonic action is applied to the liquid alloy to form a mixed melt, wherein the frequency of the ultrasonic action is 35kHz, and the power is 1000W. The mixed melt is quickly subjected to low-speed injection (at this time, the temperature of the mixed melt is 10°C above the liquidus line), the low-speed injection rate is 0.05m / s, the low-speed injection time is 8s, the high-speed injection rate is 10m / s, and the high-speed injection is performed until the mixed slurry fully fills the mold, and then the pressure is maintained, the holding pressure is 200MPa, and the holding time is 10S, so as to obtain a small part.

[0046] Example 7: The composition of the liquid alloy is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, strontium: 0.0001%, and the rest is aluminum. According to the composition of the liquid alloy, various metals are weighed and mixed, heated to 650°C, and slag and gas are removed to form a liquid alloy, which is then cooled to 40°C above the liquidus and kept warm.

[0047] The composition of the alloy powder is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, calcium: 1%, and the rest is aluminum. According to the composition of the alloy powder, various metals are weighed and mixed, heated to 650°C, and deslag and degas to form a liquid, and then formed into powder by spraying, and sieved to obtain an alloy powder with an average particle size of 5μm.

[0048] The press chamber is preheated to 400°C (the interior of the press chamber is coated with TBCs coating (yttria-stabilized zirconia YSZ coating), with a thermal conductivity of 0.93W / m·K), 2kg of liquid alloy and 0.1kg of alloy powder are poured into the press chamber, and ultrasonic action is applied to the liquid alloy to form a mixed melt, wherein the frequency of the ultrasonic action is 35kHz, and the power is 1000W. The mixed melt is quickly subjected to low-speed injection (at this time, the temperature of the mixed melt is 5°C above the liquidus line), the low-speed injection rate is 0.05m / s, the low-speed injection time is 8s, the high-speed injection rate is 8m / s, and the high-speed injection is performed until the mixed slurry fully fills the mold, and then the pressure is maintained, the holding pressure is 200MPa, and the holding time is 10S, so as to obtain small parts.

[0049] Comparative Example 1: The composition of the liquid alloy is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, strontium: 0.0001%, and the rest is aluminum. According to the composition of the liquid alloy, various metals are weighed and mixed, heated to 650°C, and slag and gas are removed to form a liquid alloy, which is then cooled to 40°C above the liquidus and kept warm.

[0050] The composition of the alloy powder is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, calcium: 1%, and the rest is aluminum. According to the composition of the alloy powder, various metals are weighed and mixed, heated to 650°C, and deslag and degas to form a liquid, and then formed into powder by spraying, and sieved to obtain an alloy powder with an average particle size of 5μm.

[0051] The press chamber was preheated to 400°C (the interior of the press chamber was not coated with a thermal insulation coating, and the thermal conductivity was 45 W / m·K). 2 kg of liquid alloy and 0.1 kg of alloy powder were poured into the press chamber, and ultrasonic action was applied to the liquid alloy to form a mixed melt. The frequency of the ultrasonic action was 35 kHz, and the power was 1000 W. The mixed melt was quickly injected at a low speed (the temperature of the mixed melt was 2°C above the liquidus line at this time). The low-speed injection rate was 0.05 m / s, the low-speed injection time was 8 s, and the high-speed injection rate was 10 m / s. The high-speed injection was performed until the mixed slurry fully filled the mold, and then the pressure was maintained. The holding pressure was 200 MPa and the holding time was 10 s to obtain small parts.

[0052] Comparative Example 2: The composition of the liquid alloy is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, strontium: 0.0001%, and the rest is aluminum. According to the composition of the liquid alloy, various metals are weighed and mixed, heated to 650°C, and slag and gas are removed to form a liquid alloy, which is then cooled to 40°C above the liquidus and kept warm.

[0053] The press chamber is preheated to 400°C (the interior of the press chamber is coated with TBCs coating (yttria-stabilized zirconia YSZ coating), with a thermal conductivity of 0.93W / m·K), 2kg of liquid alloy is poured into the press chamber, and the liquid alloy is quickly injected at a low speed (the temperature of the mixed melt is 24°C above the liquidus at this time). The low-speed injection rate is 0.05m / s, the low-speed injection time is 8s, and the high-speed injection rate is 10m / s. The high-speed injection is performed until the mixed slurry fully fills the mold, and then the pressure is maintained. The holding pressure is 200MPa and the holding time is 10S to obtain small parts.

[0054] Comparative Example 3: The composition of the liquid alloy is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, strontium: 0.0001%, and the rest is aluminum. According to the composition of the liquid alloy, various metals are weighed and mixed, heated to 650°C, and slag and gas are removed to form a liquid alloy, which is then cooled to 80°C above the liquidus and kept warm.

[0055] The composition of the alloy powder is: silicon: 6.9%, nickel: 0.01%, magnesium: 0.30%, copper: 0.005%, iron: 0.10%, zinc: 0.015%, titanium: 0.10%, manganese: 0.003%, calcium: 1%, and the rest is aluminum. According to the composition of the alloy powder, various metals are weighed and mixed, heated to 650°C, and deslag and degas to form a liquid, and then formed into powder by spraying, and sieved to obtain an alloy powder with an average particle size of 5μm.

[0056] The press chamber is preheated to 400°C (the interior of the press chamber is coated with TBCs coating (yttria-stabilized zirconia YSZ coating), with a thermal conductivity of 0.93W / m·K), 2kg of liquid alloy and 0.1kg of alloy powder are poured into the press chamber, and ultrasonic action is applied to the liquid alloy to form a mixed melt, wherein the frequency of the ultrasonic action is 35kHz, and the power is 1000W. The mixed melt is quickly subjected to low-speed injection (at this time, the temperature of the mixed melt is 57°C above the liquidus line), the low-speed injection rate is 0.05m / s, the low-speed injection time is 8s, the high-speed injection rate is 10m / s, and the high-speed injection is performed until the mixed slurry fully fills the mold, and then the pressure is maintained, the holding pressure is 200MPa, and the holding time is 10S, so as to obtain a small part.

[0057] The small parts prepared in the above examples and comparative examples were subjected to tensile strength tests and metallographic identifications, and the results are shown in Table 1. The tensile strength was measured according to the method disclosed in the national standard GB / T 228.1-2010 "Metallic material tensile test Part 1: Room temperature test method".

[0058] Table 1: Tensile strength and metallographic results.

[0059]

[0060] According to the data in Table 1, the tensile strength and metallographic results of Examples 1-7 are better than those of Comparative Examples 1-3. This is because the present solution uses a pressure chamber with an inner surface thermal conductivity of less than 10 W / m·K to prevent the liquid alloy from being locally overcooled and forming pre-crystallization after contacting the inner wall of the pressure chamber, and by adding alloy powder during the process of adding liquid alloy to the pressure chamber, and applying ultrasonic action to make the alloy powder evenly distributed in the liquid alloy to form a mixed melt 5-10°C above the liquidus line. At this time, the alloy powder and the liquid alloy have not yet fully exchanged heat. First, low-speed injection is used to avoid air entrainment of the mixed melt with a low solid phase fraction. When the injection is performed at a low speed, the injection is performed at a high speed. Under the shear force provided by the alloy powder and the local supercooling provided by the alloy powder, the liquid phase components in the mixed melt form new crystal nuclei. The evenly distributed alloy powder provides a uniform temperature field for the mixed melt. The liquid phase components nucleate around the alloy powder. Therefore, the mixed melt as a whole has a relatively uniform material field. The uniform temperature field and material field as well as the heterogeneous nucleation effect provided by the alloy powder form a refined primary phase and inhibit the rosetting and dendrite formation of the primary phase to form equiaxed crystals, thereby obtaining a semi-solid slurry with high fluidity. During high-speed injection, the semi-solid slurry with high fluidity can fully fill the interior of the mold, and finally obtain high-strength precision small parts. According to Figure 1-2It can be seen from the results that Example 1 can produce equiaxed crystals, while Comparative Example 1 has a large number of coarsened dendrites. This is because Comparative Example 1 does not use a pressure chamber with a thermal insulation coating, and the mixed melt and the pressure chamber undergo heat exchange to produce a large number of dendrites; Comparative Example 2 does not add alloy powder, which is equivalent to ordinary liquid die casting, and it is difficult to obtain high-performance castings; Comparative Example 3 uses a liquid alloy with too high a temperature. The cooling effect provided by the alloy powder alone cannot reduce the mixed melt to the semi-solid temperature range, which is also equivalent to ordinary liquid die casting, and high-quality castings cannot be obtained.

[0061] Example 2 uses alloy powder with a larger average particle size, and the tensile strength is slightly lower than that of Example 1. This is because its heat exchange efficiency is poor and the supercooling produced is small, but high-performance semi-solid castings can still be obtained compared with the comparative example. Example 6 uses alloy powder with a lower mass ratio, provides fewer nucleation sites and a smaller supercooling, and the resulting crystal nuclei are relatively coarsened, and the tensile performance is slightly lower than that of Example 1. Example 7 uses a preferred high-speed injection rate, which can fully fill the mold and produce fewer surface defects such as shrinkage cavities, and has a higher tensile strength.

[0062] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0063] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for precision preparation of small parts, characterized in that: The method comprises the following steps: preheating a pressure chamber to 300-400°C, adding a liquid alloy 20-40°C above the liquidus into the pressure chamber, adding an alloy powder with an average particle size of 5-20 μm into the pressure chamber and applying ultrasound to the liquid alloy to form a mixed melt 5-10°C above the liquidus, performing low-speed injection on the mixed melt within 5S, and then performing high-speed injection on the mixed melt, and obtaining the small parts after pressure-maintaining cooling; wherein the mass of the alloy powder is 2-10% of the mass of the liquid alloy, the rate of the low-speed injection is 0.05-0.1 m / s, the rate of the high-speed injection is 2-10 m / s, the time of the low-speed injection is 4-8S, and the thermal conductivity of the inner surface of the pressure chamber is less than 5W / m·K.

2. The preparation method according to claim 1, characterized in that: The average particle size of the alloy powder is 5-10 μm.

3. The preparation method according to claim 1, characterized in that: The mass of the alloy powder is 5%-10% of the mass of the liquid alloy.

4. The preparation method according to claim 1, characterized in that: The temperature of the alloy powder is 20-100°C.

5. The preparation method according to claim 1, characterized in that: The speed of the high-speed injection is 5-8 m / s.

6. The preparation method according to claim 1, characterized in that: The inner surface of the pressure chamber is coated with a heat insulating ceramic material.

7. The preparation method according to claim 1, characterized in that: The frequency of the ultrasound is 15-35kHz, and the power of the ultrasound is 1000-2000W.

8. The preparation method according to claim 1, characterized in that: The holding pressure is 150-200 MPa, and the holding time is 10-20S.

9. The preparation method according to claim 1, characterized in that: The liquid alloy comprises, by weight, 6.5-7.5% silicon, 0.3-0.45% magnesium, 0-0.12% iron, 0-0.05% manganese, 0-0.1% copper, 0-0.05% zinc, 0-0.2% titanium and the balance aluminum.

10. The preparation method according to claim 1, characterized in that: The alloy powder contains 1-3% by mass of a refiner.

Citation Information

Patent Citations

  • High-thermal-conductivity and high-strength aluminum matrix composite for pressure casting and preparation method of composite

    CN111719071A

  • Die casting method for inoculating semi-solid rheology in uniform acceleration pressure chamber

    CN113399642A

  • Metal powder and molten metal blending semi-solid die-casting method

    CN113680986A

  • Process suitable for semi-solid forming of high-performance small part

    CN114769548A

  • Nozzle and hot chamber die casting machine using this

    JP2007260714A